Buffalo calf rearing practices followed at peri-urban buffalo farms of Surat city, Gujarat (Indian Journal of Animal Production and Management, 2018)
A field survey was conducted to collect the information on buffalo calf rearing management practices  followed by buffalo owners in Peri-urban areas of Surat city of Gujarat. The results revealed that 98%  of the respondents attended calving and cleaned the calves soon after parturition. Ninety six percent of  respondents did not practice ligation, cutting and disinfection of the naval cord of the calf and 42% of  respondents fed colostrum to new born calf within one hour of birth. None of respondents followed weaning  practices and 42% of respondents allowed calves to suckle their dams till lactation ceased. Sixty percent  of respondents provided green fodders at the age of two months and none of respondents provided calf  starter to the calves. None of respondents practiced castration of male calves and 34% of respondents  gave anthelmetics to the calves regularly. Only 14% of respondents provided jacketing as well as bedding  in order to protect their calves from cold during winter season.
Keywords: Buffalo; Calf rearing; Management; Practices; Surat city